Pharmacologic Ascorbate Reduces Radiation-Induced Normal Tissue Toxicity and Enhances Tumor Radiosensitization in Pancreatic Cancer - Alexander, Matthew S.; Wilkes, Justin G.; Schroeder, Samuel R.; Buettner, Garry R.; Wagner, Brett A.; Du, Juan; Gibson-Corley, Katherine; O’Leary, Brianne R.; Spitz, Douglas R.; Buatti, John M.; Berg, Daniel J.; Bodeker, Kellie L.; et al. (Cancer research (Chicago, Ill.), 2018)
: Chemoradiation therapy is the mainstay for treatment of locally advanced, borderline resectable pancreatic cancer. Pharmacologic ascorbate (P-AscH , i.e., intravenous infusions of ascorbic acid, vitamin C), but not oral ascorbate, produces high plasma concentrations capable of selective cytotoxicity to tumor cells. In doses achievable in humans, P-AscH decreases the viability and proliferative capacity of pancreatic cancer via a hydrogen peroxide (H O )-mediated mechanism. In this study, we demonstrate that P-AscH radiosensitizes pancreatic cancer cells but inhibits radiation-induced damage to normal cells. Specifically, radiation-induced decreases in clonogenic survival and double-stranded DNA breaks in tumor cells, but not in normal cells, were enhanced by P-AscH , while radiation-induced intestinal damage, collagen deposition, and oxidative stress were also reduced with P-AscH in normal tissue. We also report on our first-in-human phase I trial that infused P-AscH during the radiotherapy "beam on." Specifically, treatment with P-AscH increased median overall survival compared with our institutional average (21.7 vs. 12.7 months, = 0.08) and the E4201 trial (21.7 vs. 11.1 months). Progression-free survival in P-AscH -treated subjects was also greater than our institutional average (13.7 vs. 4.6 months, < 0.05) and the E4201 trial (6.0 months). Results indicated that P-AscH in combination with gemcitabine and radiotherapy for locally advanced pancreatic adenocarcinoma is safe and well tolerated with suggestions of efficacy. Because of the potential effect size and minimal toxicity, our findings suggest that investigation of P-AscH efficacy is warranted in a phase II clinical trial. SIGNIFICANCE: These findings demonstrate that pharmacologic ascorbate enhances pancreatic tumor cell radiation cytotoxicity in addition to offering potential protection from radiation damage in normal surrounding tissue, making it an optimal agent for improving treatment of locally advanced pancreatic adenocarcinoma.